Antibiotic Resistance in Adult Patients with Urinary Tract Infection due to Escherichia Coli - Hassan, Saeeda Nabat ul; Farva, Khushbu; Bhutta, Ghulam Asghar; Khan, Rabia Naseer; Zia, Sadia; Ali, Usman (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine emerging antibiotic resistance of Escherichia Coli among isolated from the patients with urinary tract infection. Study Design: Cross-sectional study. Place and Duration of Study: Pathology Department, Sahara Medical College, Narowal Pakistan, from Mar to Aug 2022. Methodology: Two hundred cases of multi drug resistance urinary tract infection (UTI) were studied, and E. coli was isolated in their urine specimen. Cases of either gender were included with age >15 years. Data of the patients was documented on a proforma regarding demographic data, WBC count, urine culture and antibiotic susceptibility pattern result of the isolated pathogen. After detection of the pathogen (E. coli), antibiotic susceptibility patter was determined using Kirby Bauer disc diffusion method on Mueller Hinton agar. Antibiotic susceptibility of E. coli was determined against commonly used antibiotics. Results: In our study, multidrug resistant Escherichia Coli (E. coli) was detected in 139(69.5%) cases. There were 78(39.0%) males and 122(61.8%) females. Age of the patients ranged from 14-65 years, with a mean age of 33.4±9.1 years. One hundred and seventy-one (85.5%) cases were resistant to cephalosporins, 173(86.5%) to quinolones, 86(43.0%) to aminoglycosides, and 27(13.5%) were resistant to carbapenems. Conclusion: Multidrug resistant E. coli infection is common among patients with urinary tract infection. E. coli was resistant to most of the commonly used antibiotics, but it showed good sensitivity to carbipenems, penicillins and amikacin.